Influence of plasma on the physical properties of ointments with quercetin - Szulc-Musioł Beata; Dolińska Barbara; Kołodziejska Justyna; Ryszka Florian (Acta Pharmaceutica)
Effects of two independent variables - the content of quercetin (0 or 1 or 1.5 or 5 %) and the content of plasma (0 or 2 or 4 or 6 %) - on the organoleptic properties and rheological parameters of model formulations prepared on an amphiphilic base were estimated. The consistency of all ointments was uniform, and the content of quercetin and plasma lay within the predefined range. Tested ointments are non-Newtonian systems. The content of quercetin and plasma was found to have a significant effect on the rheological properties of the ointments. An increase in the content of plasma in ointments was accompanied by a significant increase in their hardness, viscosity and shear stress and a reduction of their spreadability. The best rheological properties were shown by formulation F-3, containing 1.5 % of quercetin and 2 % of plasma.